THE END OF INTIMACY. (26th August 2021) - STRONG, THOMAS
ABSTRACT: Though comparisons between HIV and SARS‐CoV‐2 are of limited use, many people experience the epidemics simultaneously. For those of us living with HIV, every comment on COVID‐19 becomes a fretful allegory of HIV, and the ethical lessons that COVID‐19 teaches will inevitably be brought to bear on how we understand the meaning of the HIV epidemic, especially as it pertains to sexuality. This essay describes some of the ways gay men in Dublin, Ireland, reasoned about the ethics of sex during lockdown.